2014
DOI: 10.1007/s12032-014-0158-6
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase reverse transcriptase (TERT) A1062T mutation as a prognostic factor in Egyptian patients with acute myeloid leukemia (AML)

Abstract: This study aimed to evaluate the incidence and clinical and prognostic impact of TERT A1062T mutation in AML patients treated at Mansoura Oncology Center. Screening for TERT A1062T mutation in exon 15 of the TERT gene was performed on diagnostic DNA samples from 153 AML patients and 197 healthy subjects as a control group by using sequence-specific primers. TERT A1062T mutation was detected in 18 cases out of 153 patients (11.8 %) and in one out of 197 control group subjects (0.51 %). The achievement of comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
4
1
Order By: Relevance
“…In our cohort of AML patients, the SNV was identified in 10/226 (4.4%) but it was also found in a similar frequency among Swedish population healthy controls 22/806 (2.7%). This mutations did not significantly alter the risk, nor affecting the OS in our AML cohort, contrary to the study by Salah et al where they identified this mutation in 18 of 153 AML patients and only in one in 197 control group subjects [ 38 ]. In the present study we also show that the TERT promoter polymorphism rs2853669 influence OS with a significantly shorter survival in AML patients with the CC genotype.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In our cohort of AML patients, the SNV was identified in 10/226 (4.4%) but it was also found in a similar frequency among Swedish population healthy controls 22/806 (2.7%). This mutations did not significantly alter the risk, nor affecting the OS in our AML cohort, contrary to the study by Salah et al where they identified this mutation in 18 of 153 AML patients and only in one in 197 control group subjects [ 38 ]. In the present study we also show that the TERT promoter polymorphism rs2853669 influence OS with a significantly shorter survival in AML patients with the CC genotype.…”
Section: Discussioncontrasting
confidence: 99%
“…None of the other analyzed TERT SNVs in our study showed any association with the risk of having AML. Recently, TERT 1062A> T SNV (rs35719940) was identified as a mutation with prognostic value and shorter overall survival and it was suggested as an independent negative prognostic factor in AML patients [ 38 ]. In our cohort of AML patients, the SNV was identified in 10/226 (4.4%) but it was also found in a similar frequency among Swedish population healthy controls 22/806 (2.7%).…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, many studies have sought to identify TERT variants in various types of cancer, as these variants could be the driver of carcinogenesis. One of the most commonly found mutation in AML is G>A conversion in codon 1062 situated at exon 15 of the TERT gene, resulting in alanine>threonine substitution (A1062T) [120][121][122][123]. AML patients with A1062T TERT mutation had a relatively poorer prognosis as this mutation is associated with shorter overall survival, higher relapse incidence, and greater rate of treatment-related toxicity [120,121].…”
Section: Tert Dysregulation and Clinical Implications In Acute Myeloid Leukemiamentioning
confidence: 99%
“…One of the most commonly found mutation in AML is G>A conversion in codon 1062 situated at exon 15 of the TERT gene, resulting in alanine>threonine substitution (A1062T) [120][121][122][123]. AML patients with A1062T TERT mutation had a relatively poorer prognosis as this mutation is associated with shorter overall survival, higher relapse incidence, and greater rate of treatment-related toxicity [120,121]. Epigenetic regulation of TERT has been the focus of many studies as it is believed to aid in the malignant transformation of cells [54].…”
Section: Tert Dysregulation and Clinical Implications In Acute Myeloid Leukemiamentioning
confidence: 99%
“…Mutations in all three telomerase core components (TERT, TERC and DKC1) have substantial effects on cell proliferation in humans, resulting in stem cell exhaustion, aging phenotypes and cancer [39][40][41][42][43] . Interestingly, mutations that impair telomere function were also found in NHP2 and NOP10, like DKC1, nucleolar factors that are associated with telomerase [44][45][46][47] .…”
Section: Research Highlightmentioning
confidence: 99%